MAKNA CINTA TERPENDAM DALAM PUISI HOSHI KARYA SHIRAISHI KAZUKO: KAJIAN SEMIOTIKA (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Poetry is a form of literary work that has unique characteristics because it is written in a dense and beautiful language, and in poetry there are often connotative and figurative words. This research discusses the contemporary poetry of Hoshi by Shiraishi Kazuko using the semiotic approach of the Ferdinand de Saussure. The data collection methods used in this research were observation and literature study methods. This poem tells the story of a writer who tries to convey a hidden feeling that he wants to express to someone. The results of the analysis on this poem shows the meaning of the signs contained in this poem describing such as: (1) how the writer feels trying to find the truth in himself, (2) is in a state of having a lot of thoughts and considerations, (3) feelings that have been buried for a long time, causing a feeling of discomfort and uncertainty (4) the writer who comprehend his feelings and his thoughts in silence, (5) the longing and hope of the character makes him want to close his eyes and fall asleep into fantasies.